RELATIONSHIP BETWEEN ROTAVIRUS AND FIMBRIATED ESCHERICHIA COLI IN ENTERIC INFECTIONS OF NEONATAL ALPACAS - Morales C, Siever (2007)
The objective of the present research was to determine the presence and the association between rotavirus, biotype E. coli and fimbriated E. coli in the enteric infections of neonatal alpacas under natural conditions. The detection of rotavirus was carried out by agglutination with monoclonal antibodies, the biotyping of E. coli by API 20E system and the detection of fimbrial antigens by agglutination using monoclonal antibodies. In 15 out of 160 (9.4%) of fecal samples from neonatal alpacas with enteric infection was detected rotavirus. Ten biotypes of E. coli was found and 26% of the E. coli isolates from alpaca neonates with enteric infection had the F41 antigen in contrast with 48% from clinically healthy neonatal alpacas. Rotavirus was found in association with 18.8% of the E. coli isolates identified as biotypes A and C. The 57.8 % of E. coli isolates from neonatal alpacas with enteric infections which contained the fimbrial antigen F41 were found in association with rotavirus. In the present research has been found that under natural conditions, rotavirus is present in conjunction with a different biotype of E. coli and fimbrial antigens F41 in 18.8%; therefore, the association between rotavirus, E. coli biotype and fimbrial antigen F41 may be the cause of diarrhea in 18.8% of 30-40% of neonatal alpacas affected.